2007
DOI: 10.1042/bj20070128
|View full text |Cite
|
Sign up to set email alerts
|

Novel xylan-binding properties of an engineered family 4 carbohydrate-binding module

Abstract: Molecular engineering of ligand-binding proteins is commonly used for identification of variants that display novel specificities. Using this approach to introduce novel specificities into CBMs (carbohydrate-binding modules) has not been extensively explored. Here, we report the engineering of a CBM, CBM4-2 from the Rhodothermus marinus xylanase Xyn10A, and the identification of the X-2 variant. As compared with the wild-type protein, this engineered module displays higher specificity for the polysaccharide xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
(38 reference statements)
1
33
0
Order By: Relevance
“…From previous studies, it is known that CBM4-2 binds both xylans and cellulosic polysaccharides. 32 Here we show that CBM4-2 can also recognize highly decorated xylans such as the FAXs used in this study, as analysed by ITC ( Fig. S2 and Table S1, ESI †) and AE (Fig.…”
Section: Affinity Of Cbms To Faxsupporting
confidence: 53%
See 1 more Smart Citation
“…From previous studies, it is known that CBM4-2 binds both xylans and cellulosic polysaccharides. 32 Here we show that CBM4-2 can also recognize highly decorated xylans such as the FAXs used in this study, as analysed by ITC ( Fig. S2 and Table S1, ESI †) and AE (Fig.…”
Section: Affinity Of Cbms To Faxsupporting
confidence: 53%
“…However, the determined affinity for FAX is about ten times lower than that previously observed for oat-spelt xylan (low arabinose/xylose ratio) and four times lower than for birchwood xylan (more decorated xylan). 32 For CBM X-2, which has previously been shown to bind different xylans at a lower affinity compared to CBM4-2, the affinity toward FAX was detected but could not be quantified with ITC. Furthermore, CBM X-2 is retained in AE gels containing FAX (Fig.…”
Section: Affinity Of Cbms To Faxmentioning
confidence: 92%
“…While investigating the binding efficiency of different variants of CBM4 from Rhodothermus marinus xylanase 10A (GH10) to unbleached pulp fibers, Filonova et al (2007a) observed that one of the variants, X-2, bound to the S1 layer at dislocations. In this experiment it is believed that the X-2 variant uses only one aromatic residue for interaction with only one face of the xylan chain (Cicortas-Gunnarsson et al 2007), i.e. that this particular variant perhaps does not have a cleft type binding mechanism.…”
Section: Bindingmentioning
confidence: 98%
“…Additional uses include highly specific probes for cell wall constituents, which are critical to refining our understanding of plant cell wall construction [6466]. …”
Section: Applications Of Phage Display In Agriculture: Seed Producmentioning
confidence: 99%